Avoid remixing step in track producing extrusion compound (atr-6112) by modification of viscosity - Thennakoon, T.M.A.D.L.; Withanage, N.S.; Abhiram, G.; Munasinghe, R.C. (University of Jaffna, 2018)
Rubber compounding has mainly master batch mixing and final batch mixing. In some special cases, rubber compounding has additional re-mixing step to achieve specific viscosity standards in master batch mixing. This extra step increases the cost negatively affecting the profit of the rubber compounding industries. In this research, avoidance of remixing step in track producing extrusion compound was focused by modifying the viscosity. Thus, the properties and processability of said compound were tested by changing mastication phase rotor speed (25 rpm, 40 rpm, 55 rpm), mastication phase masticate time (80 s 100 s, 120 s), carbon black incorporation phase rotor speed (25 rpm, 40 rpm, 55 rpm) and dispersion phase rotor speed (25 rpm, 40 rpm, 55 rpm) separately. Furthermore, viscosity properties of the compound were analyzed by using Complete Randomized Design with 4 replicates per each treatment. Results revealed that, rotor speed and mastication phase masticate time have significant effect on viscosity of the compound. Better properties could be obtained at mastication phase 55 rpm rotor speed, mastication phase masticate time 120 s and 80 s, carbon black incorporation phase 55 rpm rotor speed, dispersion phase 55 rpm and 25 rpm rotor speed. These different best level were combined and the properties were tested again. The lowest viscosity value shown at mastication phase 55 rpm, mastication time 80 sec, carbon black incorporation phase 55 rpm and dispersion phase 25 rpm was taken as best combination and was selected as the new mixing cycle. In the selected mixing cycle, carbon black incorporation phase temperature was controlled at 150 0C well. The developed new mixing cycle of master batch mixing cycle could avoid the remixing step in track producing extrusion compound (ATR-6112) by modification of viscosity.
Keywords: Master batch mixing cycle conditions; Re-mixing; Track producing extrusion compound; Viscosity modification